Ultrastructural detection of an unusual intranuclear bacterium in Pentastiridius leporinus (Hemiptera: Cixiidae) - Arneodo Larochette, Joel Demián (2008)
Pentastiridius leporinus is an important vector of sugar beet pathogens in eastern France. An electron microscope survey on the insectassociated microflora revealed the occurrence of intranuclear prokaryotic cells in every internal organ analysed. These bacteria, which could also be found in the cytoplasm surrounding the nucleus, had a homogeneous coccoid (ca. 0.45 um) or rod (0.45–1 um) shape. The presence of three membrane layers was observed, the outermost forming a kind of vacuole containing generally a single microorganism. No cytopathological abnormalities were detected in the infected cells. To our knowledge, this is the first report of a hemipteran species infected by intranuclear bacteria. The possible identity of this microorganism is discussed.